Recidivism Outcomes for Suburban Mental Health Court Defendants - Dirks-Linhorst, P. Ann (American journal of criminal justice, 2012)
Mental health courts have recently emerged as one means to reduce the number of persons with mental illness in the criminal justice system. Using a post-test only comparison group design, this study examined rearrest rates for 1 year post discharge among three groups meeting admission criteria for a municipal mental health court. The rearrest rate of defendants who successfully completed the program ( N = 351) was 14.5%, compared to 38% among defendants negatively terminated from the program ( N = 137), and 25.8% among defendants who chose not to participate ( N = 89). This positive result held even when controlling for a range of variables in a Cox regression survival analysis. Factors associated with rearrest are identified for each of the three groups.